ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMSI BUAH-BUAHAN PADA SKALA RUMAH TANGGA DI KOTA MATARAM - Azka Iklilah alhudzaifah; Anwar Anwar; Sri Maryati (JURNAL AGRIMANSION, 2021)
This research aim to analyze the quantities of melon, factors that affect the demand of melon in Mataram City and the elasticity of demand for melons due to changes in price and income. This research was conducted by purposive sampling in Mandalika Market and Cakranegara Fruit Arena. The determination of respondents are divided into two categories were melon traders and consumers of melon, for melon traders to set the entire melon trades, while for consumers of melon was conducted by in quota sampling as much as 30 people. The results of this study showed: 1) The quantities of demand for melons per household in Mataram city in February was an average of 64.75 kg. 2) Factors that influence to the quantities of demand for melon in Mataram city was the price of melons. 3) Price elasticity to demand for melons in Mataram city was 1,295 (Eh > 1) (elastic) and this causes a rise in demand for melons as much as 1.295 kg if the price goes down by 1%, while the price elasticity of revenues was 0.343 (Ep < 1) (inelastic) and this causes a rise in demand for fruit melon as much as 0.343 kg if income rises by 1%.